MENINGKATKAN KUALITAS GURU: PERAN LEMBAGA KURSUS DALAM PENGEMBANGAN PROFESIONAL PENDIDIK - Azis Hikmal Syawaludin (ADISAM PUBLISHER, 2024)
This article discusses the important role played by course institutions in improving teacher quality through educator professional development. Against the background of the complexity of the challenges faced by modern teachers in dealing with changing curricula, educational technology and diverse learning needs, course institutions become crucial partners in supporting their continuous development. Using case studies and testimonials, this article evaluates the positive impact of teacher participation in professional development programs organized by course institutions, both from the perspective of improving the quality of teaching and student learning outcomes. In addition, this article also provides recommendations for teachers in choosing professional development programs that suit their needs, as well as suggestions for course institutions in improving the quality and relevance of their programs. Thus, this article presents a comprehensive understanding of how course institutions play a role in improving the quality of teachers and their contribution to improving education as a whole.